Technology choice and international trade - Gabriela Schmidt (Kiel Institute for the World Economy (IfW), 2010)
This paper develops two extensions of the dynamic model presented in Melitz (2003). The first extension consists in the introduction of technology choice between three alternative production technologies: L, M and H. L is assumed to be the same as Melitz's single production technology, while M and H are assumed to be superior production technologies, stemming this superiority from the fact these technologies substitute the more primitive capital goods used in technology L with newer, updated versions which embody technological advances, and also from the fact that M and H are more skill-intensive than L. Technologies M and H are equally skill-intensive, but H still is superior to M because it incorporates world-technology-frontier capital goods, while the capital goods used in M are below such frontier. The second extension consists in the introduction of two different exporting profiles: 'Low-Commitment Exporters' - who make the minimum possible investment required to penetrate export markets- and 'High-Commitment Exporters' - who are ready to make additional trade-related investments in order to gain additional export sales.
Keywords: O14; O33; 330; Technology choice; heterogeneous firms; export profiles; embodied technology; resources' redistribution; monopolistic competition; Allokation; Außenwirtschaft; Markteintritt; Branchenentwicklung; Produktivität; Außenhandelsliberalisierung; Technologiewahl; Monopolistischer Wettbewerb; Theorie